Assessing the ecological health status using macrobenthic communities of tropical coastal water - Tavakoly Sany, Seyedeh Belin; Hashim, Rosli; Tajfard, Mohammad; Rahman, Mohammad Azizur (Taylor & Francis, 2018)
The relative contributions of natural and anthropogenic fluctuations are different in shaping habitat health status and natural benthic communities in tropical coastal water. Understanding responses of coastal benthic communities to these fluctuations are still equivocal and thus available data are inadequate. Here, multiple analytical approaches were used to address the significant risk factors and their impacts on coastal benthic habitat health through space and time. A total abundance of 1436 ± 612 individuals of 33 benthic species were counted and identified from 22 sampling stations across eight sampling periods over the two years of study. Bioassay results showed that the benthic community is moderately exposed to anthropogenic pollutants in Klang Strait coastal water. The results showed that there were no significant temporal changes of habitat health status and macrobenthic community structure; however, spatial changes were significant and synchronized with anthropogenic and natural fluctuations. This study demonstrates that Cd and Hg levels and sediment characteristics played the primary role in shaping the habitat health and macrobenthic assemblages, whereas the influence of other factors were insignificant.